Micro- and nano-topography to enhance proliferation and sustain functional markers of donor-derived primary human corneal endothelial cells. (June 2015) - Muhammad, Rizwan; Peh, Gary S.L.; Adnan, Khadijah; Law, Jaslyn B.K.; Mehta, Jodhbir S.; Yim, Evelyn K.F.
Graphical abstract: Abstract: One of the most common indications for corneal transplantation is corneal endothelium dysfunction, which can lead to corneal blindness. Due to a worldwide donor cornea shortage, alternative treatments are needed, but the development of new treatment strategies relies on the successful in vitro culture of primary human corneal endothelial cells (HCECs) because transformed cell lines and animal-derived corneal endothelial cells are not desirable for therapeutic applications. Primary HCECs are non-proliferative in vivo and challenging to expand in vitro while maintaining their characteristic cell morphology and critical markers. Biochemical cues such as growth factors and small molecules have been investigated to enhance the expansion of HCECs with a limited increase in proliferation. In this study, patterned tissue culture polystyrene (TCPS) was shown to significantly enhance the expansion of HCECs. The proliferation of HCECs increased up to 2.9-fold, and the expression amount and localization of cell–cell tight junction protein Zona Occludens-1 (ZO-1) was significantly enhanced when grown on 1 μm TCPS pillars. 250 nm pillars induced an optimal hexagonal morphology of HCEC cells. Furthermore, we demonstrated that the topographical effect on tight-junction expression and cell morphology could be maintained throughout each passage, and was effectively 'remembered' by the cells. Higher amount of tight-junction protein expression was maintained at cell junctions when topographic cues were removed in the successive seeding. This topographic memory suggested topography-exposed/induced cells would maintain the enhanced functional markers, which would be useful in cell-therapy based approaches to enable the in situ endothelial cell monolayer formation upon delivery. The development of patterned TCPS culture platforms could significantly benefit those researching human corneal endothelial cell cultivation for cell therapy, and tissue engineering applications.